Cytological, genetic and transcriptomic characterization of a cucumber albino mutant - Yan, Jinqiang; Liu, Bin; Cao, Zhenqiang; Chen, Lin; Liang, Zhaojun; Wang, Min; Liu, Wenrui; Lin, Yu'e; Jiang, Biao (Frontiers in Plant Science, 2022)
Photosynthesis, a fundamental process for plant growth and development, is dependent on chloroplast formation and chlorophyll synthesis. Severe disruption of chloroplast structure results in albinism of higher plants. In the present study, we report a novel cucumber albino alc mutant that presented white cotyledons under normal light conditions and was unable to produce first true leaf. Meanwhile, alc mutant could grow creamy green cotyledons under dim light conditions but died after exposure to light. No chlorophyll and carotenoid were detected in the alc mutant grown under normal light conditions. Using transmission electron microscopy, impaired chloroplasts were observed in this mutant. The genetic analysis indicated that the albino phenotype was recessively controlled by a single locus. Comparative transcriptomic analysis between the alc mutant and wild type revealed that genes involved in chlorophyll metabolism and the methylerythritol 4-phosphate pathway were affected in the alc mutant. In addition, three genes involved in chloroplast development, including two FtsH genes and one PPR gene, were found to have negligible expression in this mutant. The quality of RNA sequencing results was further confirmed by real-time quantitative PCR analysis. We also examined 12 homologous genes from albino mutants in other plant species, but no genetic variation in the coding sequences of these genes was found between alc mutant and wild type. Taken together, we characterized a cucumber albino mutant with albinism phenotype caused by chloroplast development deficiency and this mutant can pave way for future studies on plastid development.